Alternative foaming agents for topical treatment of ulcerative colitis. Issue 5 (24th January 2018) - Asama, Martin; Hall, Alex; Qi, Yijun; Moreau, Branden; Walthier, Heidi; Schaschwary, Matthew; Bristow, Blaine; Wang, Qun
Abstract: Approximately 907, 000 Americans currently suffer from ulcerative colitis, a condition characterized by inflammation of the large intestine or rectum. Treatment of this disease often includes anti‐inflammatory medication or immunosuppressants. Here foams are an attractive delivery platform, offering relatively high bioavailability, low systemic exposure, and improved patient comfort. However, the surfactants that generate these foams may adversely affect the diseased mucosa. Therefore, this project evaluated two alternative surfactants for use in topical drug delivery platforms: sodium caseinate andl ‐α‐phosphatidylcholine. Both were compared to the biocompatible surfactant Pluronic ® F‐127 using stability and density tests, and biocompatibility tests performed on mini‐guts. Sodium caseinate foams were less stable but denser than Pluronic ® foams; however, they exhibited an unexpectedly low shelf‐life.l ‐α‐phosphatidylcholine was an unsuccessful primary foaming agent owing to poor foamability at low concentrations. Mini‐gut growth rates were not significantly altered by surfactants, while morphology and an MTT assay identified Pluronic ® as the most biocompatible surfactant at higher concentrations. These results clarify the possible challenges that the tested surfactants may present in topical delivery platforms and show the relevance of permeability to tissue–surfactant interaction tests. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part A: 106A: 1448–1456, 2018.